Volcanic–plutonic connection and associated Au‐Cu mineralization of the Tulasu ore district, Western Tianshan, NW China: Implications for mineralization potential in Palaeozoic arc terranes. (9th January 2020) - Zhao, Xiao‐Bo; Xue, Chun‐Ji; Seltmann, Reimar; Dolgopolova, Alla; Andersen, Jens C. Ø.; Zhang, Guo‐Zhen
Abstract : Constructing the plutonic–volcanic connections in volcanic arc setting is essential for understanding a variety of magmatic processes from continental crust differentiation to formation of magmatic‐hydrothermal ore deposits. Based on the combination of zircon U–Pb geochronology and Hf isotope and whole‐rock geochemistry and Sr‐Nd isotopes, we evaluated the potential connections between volcanic and plutonic rocks from the Tulasu Basin, the largest epithermal gold ore district in the Chinese Western Tianshan. The peak of volcanism coincides well with the major plutonism, representing an important magma event at ~347–367 Ma. These contemporaneous volcanic and plutonic rocks show broadly similar arc‐related geochemical signatures and zircon in‐situ Hf (εHf [t] = −1.0–14.3) and whole‐rock Nd (εNd [t] = −4.2–4.6) isotopic compositions, indicative of formation from parental magmas derived from a common depleted mantle source metasomatized by slab‐derived melts, despite diverse consequent processes (fractional crystallization, crustal contamination, and magma mixing/mingling) during their differentiation in a subduction‐related setting. Volcanic rocks from the Axi caldera in the centre of the Tulasu district are geochemically less evolved than the coeval porphyritic granite, which indicates that the intrusive rocks might originate from residual melts left behind by extraction of erupted magmas. In contrast, the porphyry Cu mineralized Kexiaxi pluton, which occurs in the margin of the Tulasu district, is compositionally indistinguishable from the coeval volcanic suites. This implies that the Kexiaxi pluton represents the intrusive equivalent of a common magma reservoir feeding the volcanic eruptions, and magma fluxes may have controlled their differentiation. We thus suggest that the depleted mantle derived calc‐alkaline magma, modified during slab‐related melt metasomatism, crustal contamination, and magma mixing may have played an important role in copper enrichment at Kexiaxi. Finally, the relatively water‐rich and fertile nature of arc magma of the Tulasu district indicates high exploration potential for significant porphyry Cu‐Au deposits. The existing alteration‐immobile fertility proxy (V/Sc) for intrusive rocks may also be useful to assess the fertility of cogenetic volcanic rocks, in turn with implications for unexposed porphyry Cu deposits at depths.